First-Principles Study of Electronic Structure and Optical Properties of the $LaAlO_3/SrTiO_3$ Interfaces (Journal of Atomic and Molecular Sciences, 2013)
The electronic structure and optical properties of the perovskite oxide $LaAlO_3,$ $SrTiO_3$ and $LaAlO_3 /SrTiO_3$ interfaces were studied by the density functional theory (DFT) based on First-principles plane wave pseudopotential method. The energy band structure analysis shows that the $(AlO_2)^-/(TiO_2)^0$ interface is insulating with the band gap being 1.888 eV, whereas the $(LaO)^+/(SrO)^0$ interface seems to be a semiconductor or semimetal with the band gap being 0.021 eV. Moreover, we have also investigated optical properties of the $LaAlO_3,$ $SrTiO_3$ and $LaAlO_3/SrTiO_3$ interfaces, the results indicate that the intensities of absorption, reflectivity, and energy loss spectra of $LaAlO_3$ and $SrTiO_3$ are higher than the corresponding intensities of the $LaAlO_3 /SrTiO_3$ interfaces.
Keywords: $LaAlO_3/SrTiO_3$ interface; electronic structure; optical properties; first principles.